Elimination of Enhanced Thermal Resistance of Spheroid Culture Model of Prostate Carcinoma Cell Line by Inhibitors of Hsp70 Induction - Samideh Khoei (Cell Journal, 2010)
AbstractObjective: The purpose of this study was to investigate the enhanced thermal resistancemechanism of the DU145 tumor spheroid cultures as compared to the prostate carcinomacell line's monolayer cultures.Materials and Methods: DU145 cells were cultured either as spheroids or monolayers.Cultures were treated with hyperthermia in a precision water bath (at 43°C for 60 minutes)and/or quercetin (50 and 500 μM for monolayer and spheroid cultures respectively). Afterhyperthermic treatment, the cell viability colony forming ability, and the expression of heatshock protein 70 (Hsp70) were examined in both culture systems. Hsp70 expression wasstudied using the western blot method.Results: Our results showed that the DU145 monolayer and spheroid cell culture treatmentwith hyperthermia alone resulted in a marked survival inhibition. Furthermore, thespheroids showed a more significant resistance to hyperthermia compared to the monolayercultures (p = 0.01). They also produced more Hsp70 than the monolayer cultures.Treatment of cells with quercetin reduced the Hsp70 level in both culture systems. However,with the reduced Hsp70 levels, thermal resistance of the spheroids showed a greaterdecrease in relation to that of the monolayers.Conclusion: The results suggest that the enhanced hyperthermia resistance mechanismof the spheroid cultures compared to that of the monolayer cultures can be attributed tospheroids' Hsp70 production.